Tiktokers: Pembinaan Identiti Mahasiswa UIN KHAS JEMBER - Rizqillah, Zidah Alfi; Akhiyat (Advances in Humanities and Contemporary Studies, 2022)
Abstract: Tiktok has become one of the most popular apps in recent years. The majority of users are teenagers who want to present themselves through social media. In their search for identity, teenagers compete to use the Tiktok application. Judging from the facts on the ground, it actually has an impact from various sides, both positive and negative. Besides that, in fact Tiktok is able to form a new identity for its users, including the students of UIN KHAS Jember, who have a religious background.Keywords: Tiktok, Identity Construction, TeenagerAbstrak: Tiktok menjadi salah satu aplikasi paling popular bebarapa tahun ke belakang. Mayoritas penggunanya merupakan remaja yang ingin mempresentasikan diri mereka melalui sosial media. Dalam pencarian jati diri para remaja belomba-lomba memanfaatkan aplikasi Tiktok. Melihat dari fakta di lapangan sebenarnya memiliki dampak dari berbagai sisi, baik itu positif ataupun negatif. Selain itu nyatanya Tiktok mampu membentuk identitas baru bagi penggunanya, tidak terkecuali mahasiswa UIN KHAS Jember, yang memiliki latar belakang agamis.Kata Kunci: Tiktok, Konstruksi Identitas, Remaja